PENYIMPANAN OBAT DI GUDANG INSTALASI FARMASI RS PKU MUHAMMADIYAH YOGYAKARTA UNIT I - Solikhah, .; Sheina, Baby; Umam, M. R. (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background: Medicine arrangement in Hospital Pharmaceutical Installation included planning, procurement, distribution, and utilizing. Medicine storage indicator was : the suitability between goods and stock card, TOR (Turn Over Ratio), percentage of medicine which was expired and or damaged, storage room arrangement system, percentage of dead stock, and percentage of final stock value. Based on the result of work evaluation of Pharmaceutical Supply Inventory for tablet supply in Pharmaceutical Installation Storage Room at PKU Muhammadiyah Yogyakarta Hospital Unit I, it was found that unsuitability between goods quantity with stock card and computerization was as much as 15,38 %, TOR value was 29 times every year, final sock value was 6 %, medicine percentage was ED (expired date) 0,03 %. This data showed us that the suitability between goods and stock care, medicine ED percentage, TOR, and final stock value didnt meet the hospital target yet.Method: This research was a kind of qualitative description with a draft as observational research. The subjects at this research were The Head of Pharmaceutical Installation, The Head of Pharmaceutical Installation Storage Room, officers of Pharmaceutical Installation Storage Room, and The Head of Maintenance Unit. The means of the research used observatory method and a deep interview. Data analysis was made in a way of qualitative description, and triangulation technique was done to guarantee data validity. Results: Based on the result of research by using observation and deep interview, we knew that medicine storage system in Pharmaceutical Installation Storage Room didnt meet the standard because the medicine arrangement didnt refer to therapy class/ medicine merit. The building and the rooms were suitable with the standard, but the equipments didnt meet the standard because there was no alarm, gram and milligram measurement, box opener, and maintenance card. Human resource was already suitable with the standard because there were Pharmacist and the assistant available.Conclusion: The factor of medicine and equipment stock room system was not suitable with the standard, but the factor of building, rooms and human resource in Pharmaceutical Installation Storage Room at PKU Muhammadiyah Yogyakarta Hospital Unit I were already suitable with the standard.Keywords: Medicine storage, Building and Rooms, Equipment, Human Resource